An analysis of fluid-structure interaction for hull laminated with fibre reinforced polymer / Roslin Ramli - Ramli, Roslin (2023)
The focal point of a ship or boat is called a hull which involves the bottom parts, all sides, and the deck. Planing hull laminates are the plies which are stacked at the various orientations. Several factors affecting the hull laminate process include matrix cracking, interface debonding, delamination, or fibre breakage. The crucial factors in the selection of resin thermoset and laminates for the FRP include, durability, strength, lifetime, and the cost involved. The objectives of this study incorporate (i) to determine the optimum tensile strength for various layer stack sequences and orientations of woven roving, +45°, -45°, and 90°, (ii) to determine the initial fatigue damage leading to crack initiation by using the Fatigue Test, (iii) to verify the strength and the initial fatigue damage leading to crack initiation using Finite Element Analysis (FEA) in ANSYS Software, and (iv) to evaluate the wave impact of the wave slamming on the hull (Fluid-Structure Interaction) by using ANSYS Aqwa software. Hand lay-up was deployed to prepare the hull laminates which were stacked in sequence with an orientation where each layer is a different type of fibre mat and the orientation is at woven roving angle of +45°, -45°, and 90°.